Evolução das disparidades da extração vegetal e da silvicultura na Amazônia Legal: uma aplicação da cadeia de Markov - SANTOS, Ricardo Bruno Nascimento dos (2015)
This paper analyzes the convergence of the municipalities vegetable productivity in the Legal Amazon region between 1996 and 2006. The convergence analyses use the Markov transition matrix methodology (First Order Stationary Markov Process). The results show that existence of 13 classes of vegetable productivity convergence. In the long run, the hypothesis of absolute convergence is not maintained, whereas 68.23% of the municipalities are in a class lower than the municipal average, 33.54% in an intermediate class above average and 13.41% in a class higher than average.